From Combat Veterans to Criminals: Posttraumatic Stress Disorder and Criminal Justice Involvement - Van Nevel, Jolene M. (2017)
Posttraumatic stress disorder (PTSD) is currently known as the silent killer among combat veterans who have served in Operation Iraqi Freedom, Operation Enduring Freedom, and Operation New Dawn. Many combat veterans do not know or understand that they may be suffering from mental illness/disorders such as PTSD and turn to maladaptive behavior, resulting in criminal justice involvement (CJI). The goal of this study was to assess a relationship between PTSD and CJI among combat veterans. This study used cognitive behavior theory to understand the relationship between PTSD, CJI, and combat. This study used a predictive correlational design and statistical analysis of retrospective archival data (N=146) provided by the Department of Veteran Affairs to find the correlation between PTSD, CJI, and combat. The 5 research questions were: Does PTSD positively predict CJI in combat veterans? Does criminal history pre combat positively predict CJI in combat veterans who have PTSD? Does combat trauma experience positively predict CJI in combat veterans with PTSD? Does deployment length positively predict PTSD in combat veterans? And do multiple deployments positively predict PTSD in combat veterans? This study determined that PTSD did not significantly predict CJI and that criminal history did not predict PTSD. However, this study did predict that multiple deployments and length of deployment does predict PTSD in combat veterans. This study provides a way to bring change to how veterans are treated in the criminal justice system. This is important for many reasons, such as the positive social change it will have on the veteran community through providing insight on the changes that need to be made in PTSD awareness education and possible change in assessment and treatment of PTSD